(untitled) (Journal of Asian Development Studies, 2025)
To explore the effectiveness of webinars and workshops as teaching strategies using the Kirkpatrick model among MSN students. A qualitative phenomenological study was conducted at Ziauddin University Faculty of Nursing and Midwifery (ZUFONAM). The target population consisted of Master of Science in Nursing (MSN) students enrolled at ZUFONAM. This study adopted a quasi-experimental post-analysis design and followed a qualitative phenomenological approach. A qualitative descriptive study explored nursing students’ experiences conducting workshops and webinars as course assignments. Data were collected through semi-structured interviews with participants who shared their challenges, learning experiences, and recommendations. Thematic analysis identified key themes, including initial challenges due to ambiguity, skill development in teamwork, communication, collaboration, and technological handling, as well as suggestions for incorporating workshops and webinars into teaching strategies. This study’s findings reflect the growing importance of interactive learning strategies in nursing education. While there are still issues with the preparedness and comfort of students with new formats, the overall benefits of workshops and webinars in enhancing teamwork, communication skills, and confidence are well-documented in recent literature.